PRMT5 dimethylates R30 of the p65 subunit to activate NF-κB - Wei, Han (National Academy of Sciences, 2013)
The ubiquitous inducible transcription factor NF-κB plays central roles in immune and inflammatory responses and in tumorigenesis. Complex posttranslational modifications of the p65 subunit (RelA) are a major aspect of the extremely flexible regulation of NF-κB activity. Although phosphorylation, acetylation, ubiquitination, and lysine methylation of NF-κB have been well described, arginine methylation has not yet been found. We now report that, in response to IL-1β, the p65 subunit of NF-κB is dimethylated on arginine 30 (R30) by protein-arginine methyltransferase 5 (PRMT5). Expression of the R30A and R30K mutants of p65 substantially decreased the ability of NF-κB to bind to κB elements and to drive gene expression. A model in which dimethyl R30 is placed into the crystal structure of p65 predicts new van der Waals contacts that stabilize intraprotein interactions and indirectly increase the affinity of p65 for DNA. PRMT5 was the only arginine methyltransferase that coprecipitated with p65, and its overexpression increased NF-κB activity, whereas PRMT5 knockdown had the opposite effect. Microarray analysis revealed that ∼85% of the NF-κB–inducible genes that are down-regulated by the R30A mutation are similarly down-regulated by knocking PRMT5 down. Many cytokine and chemokine genes are among these, and conditioned media from cells expressing the R30A mutant of p65 had much less NF-κB–inducing activity than media from cells expressing the wild-type protein. PRMT5 is overexpressed in many types of cancer, often to a striking degree, indicating that high levels of this enzyme may promote tumorigenesis, at least in part by facilitating NF-κB-induced gene expression.